Automatic Door Opening and Closing System Using Arduino - Rai, Bahadur; Adhikari, Anup; Chettri, Sapna; Manger, Mansingh; Chettri, Adhishwar; Rai, Neshal (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
In these modern days opening and closing of the door have been always boring jobs, especially in a place where a person is always required to open the door for visitors such as hotels, shopping malls, and theatre. Here is a solution to open and closed the door i.e., movement sensed automatic door opening and closing system. This project is based on sensing any body movement present nearby the sensor. This is achieved with the help of an infrared sensor (IR). When a human body emits infrared energy which is detected by the IR sensor from a particular distance. The signal is detected by the sensor is pass to the controller to function a door motor IC. When a body reached the operating rate of the IR sensor, it sends a signal to the microcontroller to open and closed the door. The setting of the door is stored in the memory of the microprocessor.